2019
DOI: 10.1007/s42729-019-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Methyl Jasmonate on Photosynthetic Performance and Its Association with Antioxidants in Contrasting Aluminum-Resistant Blueberry Cultivars Exposed to Aluminum

Abstract: Methyl jasmonate (MeJA) protective effect on photosynthetic performance and its association with antioxidants in two highbush blueberry (Vaccinium corymbosum L.) cultivars with contrasting aluminum (Al) resistance under Al toxicity was determined. Legacy (Al-resistant) and Bluegold (Al-sensitive) cultivars were subjected to control, MeJA, Al, and their combination (Al+ MeJA) for 0, 24, and 48 h under greenhouse conditions. Al concentration, oxidative damage (malondialdehyde (MDA) and H 2 O 2 concentrations), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“… Ulloa-Inostroza et al (2019) also support our findings which showed that MeJA administration reduced oxidative damage through SOD. MeJA generally increases the concentration of SOD because it induces stress and hydrogen peroxide in plants ( Soares et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“… Ulloa-Inostroza et al (2019) also support our findings which showed that MeJA administration reduced oxidative damage through SOD. MeJA generally increases the concentration of SOD because it induces stress and hydrogen peroxide in plants ( Soares et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, foliar Al concentrations of 'Brigitta' were 2.6 times higher than 'Brightwell' (Table 2). High Al level in blueberry leaves could reduce photosynthesis electron transport at PSI level, and decline photosynthesis rate, therefore, influence blueberry growth (Ulloa-Inostroza, et al, 2019). In the study, similar results were found on 'Brigitta' (Table 3).…”
Section: Effect Of Al On Nutrient Uptakesupporting
confidence: 79%
“…Damage to the growth and development of plants exposed to Al is associated with oxidative damages in the membrane lipids, generally related to the increased content of hydrogen peroxide (H 2 O 2 ) (Pandey et al 2016;Ulloa-Inostroza et al 2019). Chen et al (2012) have assessed the effects of Al on Vicia faba and found that H 2 O 2 content in the roots of cultivar Anhui Candou increased by 2.3 times that of the control, after 24 h of exposure to Al.…”
Section: Discussionmentioning
confidence: 99%